Successful Management of Proctalgia Fugax through Ayurveda and Yoga: A Case Report - Kumar Pradhan, Ajit; Giri, Priyanka; Kumar Sahu, Santosh (International Research Journal of Ayurveda & Yoga, 2025)
Proctalgia fugax (PF) is a functional and recurrent anorectal pain lasting from seconds to minutes without organic pathology for more than 3 months with unknown etiology. Based on the origin and nature of pain, it resembles Tuni in Ayurveda. We report a case of a 47-year-old female previously diagnosed with PF, which did not improve after 2 months of conservative treatment, treated with Ayurvedic medicines, therapies, and the practice of Ashwini Mudra (AM). The symptoms completely resolved after 3 months of treatment. The recurrent episodes of pain were not reported after 5 months of follow-up. No adverse events were reported during the treatment. Ayurvedic management and AM could be treatment options for PF. Further future studies in large-scale patient populations are needed to gather evidence.